Peningkatan Nilai-Nilai Spiritualitas Siswa melalui Metode Pembiasaan di SMK Daya Wangsa Wonogiri: Improvement of Students’ Spirituality Values through Habitation Methods at SMK Daya Wangsa Wonogiri - Amir Mukminin; Abdul Rochman; Ratih; Uliyatul Marfu'ah; Suliwati (TA'LIMUNA: Jurnal Pendidikan Islam, 2024)
This article discusses the habituation of spirituality for students at SMK Daya Wangsa Wonogiri, in order to produce students who have both intellectual and spiritual competence, so that in the future students will become role models in community life. This article uses qualitative methods. Data collection techniques use observation, interviews and documentation. There are three research results. First, spirituality at SMK Daya Wangsa Wonogiri is carried out through the congregational Dhuha and Zhuhr prayer; and recite Al-Qur’an before lessons begin. Second, teachers play an important role in spiritual habituation activities, through their role as role models, educators and givers of rewards and punishments. Third, supporting factors for the habit of spirituality include the role of teachers, student awareness, adequate facilities, a conducive environment and cooperation from various stakeholders. Meanwhile, factors inhibiting the habit of spirituality include students’ different backgrounds, not being fluent in reciting Al-Qur’an, being late and being absent intentionally. Artikel ini membahas tentang pembiasaan spiritualitas bagi siswa di Sekolah Menengah Kejuruan (SMK) Daya Wangsa Wonogiri, dalam rangka mencetak siswa yang memiliki kompetensi intelektual sekaligus spiritual, agar kelak siswa menjadi teladan di kehidupan masyarakat. Artikel ini menggunakan metode kualitatif. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Ada tiga hasil penelitian. Pertama, pembiasaan spiritualitas di SMK Daya Wangsa Wonogiri dilakukan melalui kegiatan shalat sunah Dhuha dan shalat Zhuhur berjamaah; serta mengaji Al-Qur’an sebelum pelajaran dimulai. Kedua, guru berperan penting dalam kegiatan pembiasaan spiritualitas, melalui perannya sebagai teladan, pendidik serta pemberi penghargaan dan hukuman. Ketiga, Faktor pendukung pembiasaan spiritualitas meliputi peran guru, kesadaran siswa, fasilitas yang memadai, lingkungan yang kondusif dan kerjasama berbagai pihak. Sedangkan faktor penghambat pembiasaan spiritualitas meliputi latar belakang siswa yang beragam, belum lancar mengaji, terlambat dan absen secara sengaja. Kata Kunci: Metode Pembiasaan; Nilai-Nilai; SMK Daya Wangsa; Spiritualitas Siswa.